2016
DOI: 10.5194/tc-10-371-2016
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of snow density measurements: bias, precision, and vertical resolution

Abstract: Abstract. Density is a fundamental property of porous media such as snow. A wide range of snow properties and physical processes are linked to density, but few studies have addressed the uncertainty in snow density measurements. No study has yet quantitatively considered the recent advances in snow measurement methods such as micro-computed tomography (µCT) in alpine snow. During the MicroSnow Davos 2014 workshop, different approaches to measure snow density were applied in a controlled laboratory environment … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
96
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(117 citation statements)
references
References 57 publications
(88 reference statements)
8
96
0
Order By: Relevance
“…Our assigned uncertainty in the top meter is the relative standard deviation in observed density (12 %), which we assume is due to the natural variability in surface density. This uncertainty is higher than the assumed mean measurement uncertainty of 2-5 % (Proksch et al, 2016) and smaller than the mean difference between the modeled and observed values within the top meter (16 %). No spatial bias is evident between the mean model used here in the top 1 m of snow/firn and the observed density.…”
Section: Determining the Density Profile And Uncertaintiesmentioning
confidence: 84%
“…Our assigned uncertainty in the top meter is the relative standard deviation in observed density (12 %), which we assume is due to the natural variability in surface density. This uncertainty is higher than the assumed mean measurement uncertainty of 2-5 % (Proksch et al, 2016) and smaller than the mean difference between the modeled and observed values within the top meter (16 %). No spatial bias is evident between the mean model used here in the top 1 m of snow/firn and the observed density.…”
Section: Determining the Density Profile And Uncertaintiesmentioning
confidence: 84%
“…They showed a 7% coefficient of variation of 92 SWE estimates conducted with combined depth and density measurements. This is a result of a 1 cm standard uncertainty of snow depth measurements and a typical 5% standard relative uncertainty of gravimetric snow density measurements with density cutters and portable dynamometers in the field [22]. Rain gauge types are: manual rain gauge with 1000 cm 2 hole and melting snow operation made at the measurement time (P1); manual rain gauge (1000 cm 2 ) in a heated housing SIAP model (P2); mechanical tipping-bucket recording gauge (1000 cm 2 ) SIAP or Salmoiraghi in a heated housing SIAP model (P3); CAE PMB2 electronic tipping-bucket recording heated gauge (1000 cm 2 ) (P4).…”
Section: Case Study and The Error Estimatementioning
confidence: 99%
“…Traditional snow sampling techniques (snow pits, snow core surveys) [ Goodison et al ., ; Kinar and Pomeroy , ; Proksch et al ., ] are invasive, labor intensive, and suffer from several drawbacks like small support, large spacing and/or low repeat frequency. A number of automated in situ measurements for snow depth (SD), snow water equivalent (SWE), or liquid water content exist [ Johnson and Marks , ; Stähli et al ., ; Egli et al ., ; Lundberg et al ., ; Koch et al ., ] but are usually limited to a very small support with a high sensitivity to local anomalies.…”
Section: Introductionmentioning
confidence: 99%